Development of a Mechanism of a Piping Inspection Robot - OOYAMA, Chikara; YUKAWA, Toshihiro; OKANO, Hideharu; KOMATSUBARA, Shogo (Transactions of the Japan Society of Mechanical Engineers Series C, 2005)
The piping inspection sometimes must be performed in places such as areas of radiation contamination and at dangerous heights, etc. In an environment in which a human cannot work, a robot is needed. Up to now, many robots that inspect the inside of piping have seen practical use. On the other hand, a robot intended to inspect the surface of piping has not been realised. It has been impossible for a robot to inspect a pipe's surface due to obstacles such as flanges, valves, curves, vertical piping, etc. The present study examines a mechanism intended to allow an inspection robot to move automatically along the outside of a pipe. We have also designed a mechanism that enables the robot to correspond to traverse flanges. This robot moves by means of magnetic wheels, and is composed of three connected units. This robot can traverse flanges by moving each of its three units; i. e., one unit moves up and down while another moves horizontally.